2015
DOI: 10.1016/j.devcel.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Jmjd3-Mediated H3K27me3 Dynamics Orchestrate Brown Fat Development and Regulate White Fat Plasticity

Abstract: SUMMARY Progression from brown preadipocytes to adipocytes engages two transcriptional programs: the expression of adipogenic genes common to both brown fat (BAT) and white fat (WAT), and the expression of BAT-selective genes. However, the dynamics of chromatin states and epigenetic enzymes involved remain poorly understood. Here we show that BAT development is selectively marked and guided by repressive H3K27me3, and is executed by its demethylase Jmjd3. We find that a significant subset of BAT-selective gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 60 publications
2
78
0
Order By: Relevance
“…Mass spectrometrybased analysis of the human proteome (Proteomics DB) has demonstrated that heart, pancreas, lymphocytes, and colon express RREB1 ( 38 ). The role of RREB1 in regulation of blood glucose and atherosclerosis is unknown, but interestingly, RREB1 was recently demonstrated to modify histones by aiding in removal of histone H3 lysine 27 trimethylation (H3K27me3) marks, which often characterize silenced regions, thereby promoting Ucp1 and Cidea expression in brown adipocytes ( 39 ). This mechanism of action of RREB1 was shown to be due to recruitment of Jmjd3, an H3K27me3 demethylase.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometrybased analysis of the human proteome (Proteomics DB) has demonstrated that heart, pancreas, lymphocytes, and colon express RREB1 ( 38 ). The role of RREB1 in regulation of blood glucose and atherosclerosis is unknown, but interestingly, RREB1 was recently demonstrated to modify histones by aiding in removal of histone H3 lysine 27 trimethylation (H3K27me3) marks, which often characterize silenced regions, thereby promoting Ucp1 and Cidea expression in brown adipocytes ( 39 ). This mechanism of action of RREB1 was shown to be due to recruitment of Jmjd3, an H3K27me3 demethylase.…”
Section: Discussionmentioning
confidence: 99%
“…A significant subset of BAT-selective genes, including key thermogenic transcriptional regulators such as Prdm16, PparĪ±, and Pgc1Ī², was marked by H3K27me3 at their promoter/enhancer regions in brown preadipocytes (Pan et al, 2015). We surmised that potential thermogenic regulators might possess a similar pattern of H3K27me3 modification and gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…We surmised that potential thermogenic regulators might possess a similar pattern of H3K27me3 modification and gene expression. We therefore analyzed published chromatin immunoprecipitation sequencing (ChIP-seq) (GEO: GSE55469) and RNA sequencing (RNA-seq) (GEO: GSE56367) datasets (Pan et al, 2015), and we identified Cbx4 as a candidate. As shown in Figure 1A, Cbx4 promoter was modified by H3K27me3 in brown preadipcoytes, and this modification was largely removed in mature brown adipocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations